2016
DOI: 10.14687/jhs.v13i3.4111
|View full text |Cite
|
Sign up to set email alerts
|

Violence faced by nursing students in clinical practicals and its effects: A questionnaire survey

Abstract: Nursing students may be exposed to all the kinds of violence in clinical practice areas. Purpose: This study was conducted in order to determine the violence faced by nursing students in clinical practice areas, its effect on the gender factor and the feelings and behavior of students after the violence. Methods: The study took place at a Foundation University in Bolu, Turkey over the period 2013-2014. The students' levels of voilence were assessed second, third and fourth years of the program. The research po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…Nursing students are also being exposed to patient aggression and violent behavior, but data on their experiences are limited, may be combined with registered nurses/health care workers, or primarily exists outside of the United States. Literature outside of the United States regarding nursing student exposure to aggression or violent behavior in the health care setting reveals a large percentage of students being exposed to verbal, physical, and sexual harassment by both patients and patient family members, with verbal aggression as the most common type of aggression experienced 3,8–12. Nursing student exposure to verbal, physical, and sexual harassment at the hands of patients or patient family members leaves feelings of shame, fear, anxiety, and humiliation 9,10.…”
Section: Wpv Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…Nursing students are also being exposed to patient aggression and violent behavior, but data on their experiences are limited, may be combined with registered nurses/health care workers, or primarily exists outside of the United States. Literature outside of the United States regarding nursing student exposure to aggression or violent behavior in the health care setting reveals a large percentage of students being exposed to verbal, physical, and sexual harassment by both patients and patient family members, with verbal aggression as the most common type of aggression experienced 3,8–12. Nursing student exposure to verbal, physical, and sexual harassment at the hands of patients or patient family members leaves feelings of shame, fear, anxiety, and humiliation 9,10.…”
Section: Wpv Exposurementioning
confidence: 99%
“…Harsh language and threatening words or gestures are considered some behaviors of verbal aggression, whereas verbal sexual harassment is described as uninvited or unwelcome words, glances, and gestures with sexual content. Physical aggression is defined as forceful actions such as hitting, pushing, kicking, or spitting 3…”
mentioning
confidence: 99%
“…Through clinical practice, tutors simplify students' application of theoretical classroom knowledge in the real world such hospitals, health departments, or other healthcare settings (1) , but during clinical training the nursing students may be exposed to all kinds of violence. The most serious of which is the sexual harassment (2) .…”
Section: Introductionmentioning
confidence: 99%
“…One of them is a study that was conducted in Pakistan by Khan et al (17) who found about seventy percent of students were exposure to sexual harassment in clinical field. Another study done in Turkey by Dikmen, et al (2) assesses the violence faced by nursing students in clinical practical which also pointed that the majority of nursing students in clinical places were exposed to all kind of violence during their training. In the study done in Egypt by Hussein, et al (18) assesses the workplace sexual harassment against female nurses and occupational health outcomes who reported that harassment against nurses is endemic phenomena in Egypt and it has become an unpleasant experience for most women in our society, even at workplaces and nurses are not immune.…”
Section: Introductionmentioning
confidence: 99%
“…Workplace violence against healthcare workers is an increasing global problem (1,2). Workplace violence against nursing students has been reported to be high in international studies, indicating that students are at a high risk of exposure to violence (3)(4)(5). Violence against nursing students may occur in both clinical and academic settings (6).…”
mentioning
confidence: 99%